2007
DOI: 10.1111/j.1525-1470.2007.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Acanthosis Nigricans: A Common Finding in Overweight Youth

Abstract: We evaluated the prevalence of acanthosis nigricans among urban youth. Youth (7-17 years) at nine pediatric practices completed surveys on demographics and family history of diabetes and had weight and height measured. Acanthosis nigricans was scored and digital photography of the neck performed. A total of 618 youth were included in the analysis: mean age 11.5 years; 51% female; 61% African American, 27% Hispanic, 12% Caucasian, and 32% with body mass index >or=95th percentile. Acanthosis was found in 19%, 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 20 publications
3
47
0
2
Order By: Relevance
“…AN prevalence rates depend upon child age and race, likely related to different prevalence rates of hyperinsulinemia. For example, one study found that in children aged 7-17 who visited urban primary care practices, between 4% and 23% were diagnosed with the presence of AN, [27] these rates being the lowest among Caucasian youths and the highest among African-American and Hispanic youths.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…AN prevalence rates depend upon child age and race, likely related to different prevalence rates of hyperinsulinemia. For example, one study found that in children aged 7-17 who visited urban primary care practices, between 4% and 23% were diagnosed with the presence of AN, [27] these rates being the lowest among Caucasian youths and the highest among African-American and Hispanic youths.…”
Section: Introductionmentioning
confidence: 96%
“…The presence of AN is strongly associated with elevated BMI in children, [13,27,28] with prevalence rates approximately at 66% among adolescents greater than 200% of ideal weight. [14] It is generally believed that AN is caused by hyperinsulinemia which in turn is associated with obesity.…”
Section: Introductionmentioning
confidence: 98%
“…This high prevalence was also expected in our study with a majority of the participants being of African descendants. When BMI and ethnicity were combined, other studies [50][51][52], found that children of any race had a 62% prevalence of AN if their BMI is greater than the 98 th percentile. Higgins [49] postulate that "the association of AN with IR may be due to high concentrations of insulin producing a potent proliferative effects by binding to Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Tip 2 diabetli çocuklar-da %90, obez çocuklarda %32 oranında akantozis nigrikans gelişimi gözlenmiştir. AN diabete ek olarak diğer endokrinopatilere, niasin başta olmak üzere ilaçlara ve nadiren de malinitelere bağlı olarak gelişebilir (25). AN deri katlantılarında simetrik, kahverengi, belirsiz sınırlı, kadifemsi kalınlaşma olan plaklar şeklinde gözlenir.…”
Section: Akantozis Nigrikansunclassified